2024
DOI: 10.1186/s12876-024-03143-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for gastroesophageal reflux disease: a population-based study

Sepehr Sadafi,
Ali Azizi,
Yahya Pasdar
et al.

Abstract: Background Gastroesophageal reflux disease (GERD) in the long term reduces the quality of life, leading to digestive diseases. The present study aims to determine the risk factors for GERD. Method This study was conducted on 9,631 adults aged 35–65 years. The demographic characteristics, behavioral habits, nutritional intake, physical activity, anthropometric indices, and GERD data were extracted from the databank related to the Ravansar non-commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Multiple studies identi ed smoking as a risk factor for GERD. 75,78,96,98,113 Kim, Jang, et al interestingly found that former smoking was signi cantly associated with risk of GERD, while current smoking was not signi cantly associated. 83 When investigating gender-speci c differences on the effects of smoking on the risk of GERD, Kim, Jung, et al found that smoking increased risks in both men and women.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies identi ed smoking as a risk factor for GERD. 75,78,96,98,113 Kim, Jang, et al interestingly found that former smoking was signi cantly associated with risk of GERD, while current smoking was not signi cantly associated. 83 When investigating gender-speci c differences on the effects of smoking on the risk of GERD, Kim, Jung, et al found that smoking increased risks in both men and women.…”
Section: Methodsmentioning
confidence: 99%